Peran Pendidik dalam Pemanfaatan E-Learning di Era Society 5.0 - Haris, Muhammad (Lembaga Intelektual Muda (LIM) Maluku, 2022)
The aim of this research is to discuss the role of teachers in the use of e-learning in the era of society 5.0. The type of research carried out is library research with a qualitative approach, data collection techniques using documentation methods. The results of this research show that the role of educators in the learning process is very important, where an educator in the Society 5.0 era is required to be familiar with learning technology such as the media used in this research, namely e-learning. E-learning is an electronic-based learning method known as e-learning using an internet network between computers. Because students are taught by educators, educators must create a learning process in such a way. The teaching profession is also a component that is very familiar to us and is closely related to the world of education. Education is already facing significant obstacles today. The conclusion is the role of educators in the learning process with e-learning technology. The shifting roles of educators and students have changed due to advances in communication technology; If previously learning was dominated by educators, learning is now dominated by students.